Expectations and Satisfaction of Tourism Influencing Klong Mahasawat Floating Market, Bann Sala Din in Phutthamonthon District, Nakhon Pathom - Thongrawd, Chairit (Dusit Thani College Journal, 2020)
The purpose of this research was to study the influence of tourists’ expectations and satisfaction to Tourism of Klong Mahasawat Floating Market, Baan Sala Din in Phutthamonthon District, NakhonPathom. Sample groups used for qualitative research approach were 3 representatives from Government units and from entrepreneurs by in depth interviews. On the other hand, sample groups from quantitative research approach were 400 Thai tourists visiting Klong Mahasawat Floating Market, Baan Sala Din. Statistical data analysis implemented frequency counts, percentage, average, standard deviation, t-test, One - way ANOVA and Pearson correlation coefficient. The research results found that: Respondent came to Klong Mahasawat Floating Market, Baan Sala Din on one-day-trip by cars with family members since it was convenient and not far from Bangkok. They learned of the market from websites or social circles. Activities most liked by tourists were seeing lotus farms. Next to that was seeing orchid gardens. In the future, they thought they would certainly come back to visit and would suggest and introduce others to tour the market also. The tourists had expectations towards touring of Klong Mahasawat Floating Market, Baan Sala Din, on overall, at a medium level while on physical aspect they had an expectation at a high level. On other aspects, the tourists had expectations at a medium level i.e. personnel, products, procedure, promotion, pricing, and location, in that order. Besides, the tourists had satisfaction of tourism of Klong Mahasawat Floating Market, Baan Sala Din both on overall and each aspect at a high level i.e. personnel, products, promotion, procedure, pricing, physical characteristic, and distribution channels, in that order. The results of testing hypotheses found that: the tourists with different gender, age, education, profession, and monthly earning had different expectations towards touring Klong Mahasawat Floating Market, Baan Sala Din on overall at a statistically significant at .05 level; the tourists with different gender, age, education, and monthly earning had different satisfaction towards touring Klong Mahasawat Floating Market, Baan Sala Din on overall at a statistically significant at .05 level. Nevertheless, the tourists with different profession did not have different satisfaction towards touring on overall at a statistically significant at .05 level.